2013
DOI: 10.1021/jm4001852
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Pyrrolobenzodiazepine–Polyamide Conjugate with Selectivity for a DNA Sequence Containing the ICB2 Transcription Factor Binding Site

Abstract: The binding of nuclear factor Y (NF-Y) to inverted CCAAT boxes (ICBs) within the promoter region of DNA topoisomerase IIα results in control of cell differentiation and cell cycle progression. Thus, NF-Y inhibitory small molecules could be employed to inhibit the replication of cancer cells. A library of pyrrolobenzodiazepine (PBD) C8-conjugates consisting of one PBD unit attached to tri-heterocyclic polyamide fragments was designed and synthesized. The DNA-binding affinity and sequence selectivity of each com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The C8-position of the A ring of PBD is the most preferred point of attachment of substituents within the compound's framework. Several chemical scaffolds, including heterocyclic polyamides [13][14][15], biaryl-units [16], benzofused rings [17] and quinazolinone [18] rings have been linked to the C8 position of PBD monomer producing compounds with improved DNA-sequence selectivity [13,16], and antimicrobial [19,20], anticancer [16] and antitubercular [21][22][23] activities compared to the PBD unit alone. The shape and physicochemical properties of C8-substituents have a direct effect on the cytotoxicity of the PBD-conjugates and their ability, or inability, to interact with the DNA-minor groove and inhibit transcription factors activity [13].…”
Section: Introductionmentioning
confidence: 99%
“…The C8-position of the A ring of PBD is the most preferred point of attachment of substituents within the compound's framework. Several chemical scaffolds, including heterocyclic polyamides [13][14][15], biaryl-units [16], benzofused rings [17] and quinazolinone [18] rings have been linked to the C8 position of PBD monomer producing compounds with improved DNA-sequence selectivity [13,16], and antimicrobial [19,20], anticancer [16] and antitubercular [21][22][23] activities compared to the PBD unit alone. The shape and physicochemical properties of C8-substituents have a direct effect on the cytotoxicity of the PBD-conjugates and their ability, or inability, to interact with the DNA-minor groove and inhibit transcription factors activity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of a thermallyinduced cleavage assay, they reported that 3 forms cross-links at the 5'-AATTTTCC(G)-3' sequence. During the past six years we have developed molecular dynamics simulation methodologies [11,13,48] that allow us to accurately predict and interpret how both mono-alkylating and DNA cross-linking agents of this type interact in the minor groove of DNA. As the hybrid dimer 3 reported by Lee [47] had a significantly lower DNA cross-linking potency and in vitro cytotoxicity compared to the Hurley (1) and Denny (2) dimers, we decided to use our simulation methodologies to compare the interaction of the three molecules at their proposed DNA recognition sites.…”
Section: Introductionmentioning
confidence: 99%
“…Through the years, many novel cross-linking agents have been designed, synthesized and evaluated [4] , [5] in an attempt to (a) improve on cross-linking efficiency [6], (b) modify the sequence-selectivity of cross-linking [7], (c) change the distribution of inter-versus intrastrand cross-links [8][9][10], and/or (d) target different base pair combinations [11][12][13]. For example, the naturally occurring pyrrolobenzodiazepine (PBD) molecules, derived from Streptomyces species [14][15][16][17][18], are characterized by an N10-C11 imine group that enables formation of a covalent bond to the C2-amino group of a guanine base [19], and these have been successfully incorporated into PBD dimer structures such as DSB-120 [20] and SJG-136 [21] (Figure 1A) that can form sequence-selective G-G cross-links in the DNA minor groove.…”
mentioning
confidence: 99%
“…, isohelicity) to fit perfectly into the DNA minor groove. PBD/DNA adduct formation has been shown to inhibit a number of biological processes, including the binding of transcription factors to DNA [9], [10], [11], [12] and the function of enzymes such as endonucleases [13], [14] and RNA polymerase [15]. Many PBD molecules also have significant antimicrobial activity [16], [17], [18], [19], [20], [21].…”
Section: Introductionmentioning
confidence: 99%